Case report: Treatment response of NF-1-associated bladder ganglioneuroma to trametinib - Chan, Marcus C. Y.; Fung, Kevin K. F.; Ng, Wai-Fu; Luk, Ho-Ming; Ku, Dennis T. L.; Liu, Anthony P. Y. (Frontiers in Oncology, 2024)
We present the clinical course of a four-year-old girl with neurofibromatosis type 1-associated, unresectable, symptomatic urinary bladder ganglioneuroma. She was initially trialed on sirolimus without response, and subsequently responded to MEK inhibitor trametinib, with improvement clinically and radiographically over ten months. This report broadens the repertoire of therapeutic strategies for MEK inhibition in diseases related to the MAPK pathway.